INNOVATION IN ENERGY: CHALLENGES AND PROSPECTS - S.F. Krutous; B.M. Bekmagambetova; N.Yu. Kolesnichenko; D.K. Imangazinova (Academic Journal of Physical and Chemical Sciences, 2019)
One of the industry's most pressing innovation needs is energy digitalization. Right now, power engineers need to develop domestic software for managing electric networks and micro energy systems, information security systems of critical infrastructure, data analysis technology and predictive analytics. World crisis and energy. Oil reserves are depleted. Experts say that it will end on the planet with a continuing level of consumption in 20-30 years. There are more optimistic forecasts that indicate the existence of a large number of undiscovered reserves and the possibility of increasing production efficiency.